Administration of Eucalyptus to Inhibit the Skin Aging Process of Rats (Rattus Norvegicus) Wistar Strains Exposed to Ultraviolet-B Light - Asira Mahrahmi; Tan Suyono; Ali Napiah Nasution (CV. Inara, 2024)
Ageing weakens the skin's protective layer, causing pigmentation, inflammation, and cancer. Environmental hazards like pollution and UV radiation harm the skin. Antioxidants, like Eucalyptus globulus, protect against free radicals, making them valuable in medicinal use. The study aimed to investigate the efficacy of Eucalyptus administration in inhibiting skin ageing in rats exposed to ultraviolet-B light. A true experiment was conducted to examine the effectiveness of Eucalyptus in reducing skin ageing in Wistar rats exposed to ultraviolet-B radiation. The study used the